2022
DOI: 10.2298/ciceq210125021m
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer studies of Al2O3/water-ethylene glycol nanofluid using factorial design analysis

Abstract: The experimental study of heat transfer coefficient of nanofluid plays a significant role in improving the heat transfer rate of the heat exchanger. The research was conducted in a natural convection heat transfer apparatus by suspending Al2O3 nanoparticle in a base fluid of Water-Ethylene glycol mixture. The effects of heat input (A), nanoparticle volume fraction (B), and base fluid concentration (C) on experimental heat transfer coefficient (hexpnf) were studied. By the results obtained by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Study concluded that the thermal conductivities of nanoparticle-fluid mixtures increase significantly with the addition of nanoparticle and more studies on heat transfer in the fluid flow is needed to extract its maximum benefit. Experimental studies on thermal conductivity and heat transfer were done in a natural convection heat transfer apparatus [13,14] with a base fluid (Ethylene Glycol-Water Mixture) and observed significant enhancement in heat transfer coefficient as well as thermal conductivity. Heat transfer effect of Al2O3 nanoparticle with volume fractions of 0.25, 0.5, 0.75, and 1 vol.% was analyzed [15] and observed an increase in Nusselt number with respect to the Reynolds number and volume fraction.…”
Section: Introductionmentioning
confidence: 99%
“…Study concluded that the thermal conductivities of nanoparticle-fluid mixtures increase significantly with the addition of nanoparticle and more studies on heat transfer in the fluid flow is needed to extract its maximum benefit. Experimental studies on thermal conductivity and heat transfer were done in a natural convection heat transfer apparatus [13,14] with a base fluid (Ethylene Glycol-Water Mixture) and observed significant enhancement in heat transfer coefficient as well as thermal conductivity. Heat transfer effect of Al2O3 nanoparticle with volume fractions of 0.25, 0.5, 0.75, and 1 vol.% was analyzed [15] and observed an increase in Nusselt number with respect to the Reynolds number and volume fraction.…”
Section: Introductionmentioning
confidence: 99%